Outcomes of Endovascular Aneurysm Repair Using the Anaconda Stent-Graft. (June 2020) - Tigkiropoulos, Konstantinos; Stavridis, Kyriakos; Lazaridis, Ioannis; Bontinis, Evangelos; Zournatzi, Ioulia; Kolaki, Nikoletta; Karamanos, Dimitrios; Saratzis, Nikolaos
Purpose: To report outcomes of elective endovascular aneurysm repair (EVAR) using the Anaconda stent-graft in a tertiary vascular center.Materials and Methods: A retrospective study was conducted of 271 patients (mean age 71.5 years; 260 men) who underwent elective EVAR for abdominal aortic aneurysm using the Anaconda stent-graft from January 2006 to January 2017. Median aneurysm diameter was 58 mm (range 50–90). All patients were anatomically suitable for EVAR according to the 2003 version of the instructions for use. Follow-up included computed tomography angiography at 1, 6, and 12 months and yearly thereafter for the first 4 years and then every 2 years. Primary outcomes included technical success and 30-day aneurysm-related mortality and complications; secondary outcomes were overall and aneurysm-related mortality and aneurysm-related morbidity in follow-up.Results: The Anaconda stent-graft was implanted successfully in all patients. Primary and secondary technical success rates were 99.6% and 100%, respectively. Three patients (1.1%) died within 30 days of causes unrelated to the aneurysm, while 15 patients (5.5%) suffered perioperative complications. Median follow-up was 72 months (range 14–141). The overall type I endoleak rate was 4.7% (11 proximal, 2 distal). Late aneurysm-related complications were observed in 48 patients (17.3%); aneurysm-related mortality was 1.4% (n=4). Non-aneurysm-related mortality was 21.0% (n=57). Freedom from reintervention was 95.2% at 1 year, 98% at 2 years, and 90% at 6 years. There was no significant difference in the overall limb graft occlusion rate between the second- and third-generation devices.Conclusion: Results in our cohort study demonstrate that the Anaconda stent-graft has satisfactory early and late results with low aneurysm-related mortality.